2015
DOI: 10.1186/s12867-015-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

The elongation factor eEF3 (Yef3) interacts with mRNA in a translation independent manner

Abstract: BackgroundmRNA binding proteins (RBPs) constitute 10–15 % of the eukaryotic proteome and play important part in post-transcriptional regulation of gene expression. Due to the instability of RNA and the transient nature its interaction with RBPs, identification of novel RBPs is a significant challenge. Recently, a novel methodology for RBP purification and identification (termed RaPID) was presented, which allows high affinity purification of RBPs while associated with mRNA in vivo.ResultsWe performed a RaPID s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Another optimized in vivo system, RBP purification and identification (RaPID), uses a novel fusion protein, MS2cp-GFP-SBP, which enables both affinity purification of RNA–protein complexes using streptavidin-conjugated beads due to interaction with SBP and visualization of intracellular localization of target mRNAs bearing the MS2 aptamer using microscopy due to a fluorescence reporter (MS2cp-GFP) (44,77). Specific and strong binding of MS2cp to the MS2 loops and of SBP to streptavidin as well as formaldehyde crosslinking allows for stringent washing conditions, which prevent isolation of nonspecific RNA–protein interactions.…”
Section: Purification Of In Vitro- and In Vivo-assembled Rna–protein mentioning
confidence: 99%
See 1 more Smart Citation
“…Another optimized in vivo system, RBP purification and identification (RaPID), uses a novel fusion protein, MS2cp-GFP-SBP, which enables both affinity purification of RNA–protein complexes using streptavidin-conjugated beads due to interaction with SBP and visualization of intracellular localization of target mRNAs bearing the MS2 aptamer using microscopy due to a fluorescence reporter (MS2cp-GFP) (44,77). Specific and strong binding of MS2cp to the MS2 loops and of SBP to streptavidin as well as formaldehyde crosslinking allows for stringent washing conditions, which prevent isolation of nonspecific RNA–protein interactions.…”
Section: Purification Of In Vitro- and In Vivo-assembled Rna–protein mentioning
confidence: 99%
“…Another advantage of RaPID analysis is simple and specific elution of RNP complexes by competition with biotin. Additionally, to avoid MS2cp aggregation following high expression levels, genes encoding fusion proteins were placed under the control of an inducible promoter, which allow tightly regulated stable expression in both yeast and mammalian cells (44,77). …”
Section: Purification Of In Vitro- and In Vivo-assembled Rna–protein mentioning
confidence: 99%
“…However, the insertion of a long sequence of MS2 loops may cause changes in the processing and structure of the RNA; it might destabilize the transcript or change the repertoire of RBPs bound to it. In our experience, 12 loops are sufficient to get an efficient elution of MS2-tagged RNA 20 . In this respect, we note that we usually observed additional shorter transcripts in our northern hybridizations.…”
Section: Discussionmentioning
confidence: 93%
“…In this respect, we note that we usually observed additional shorter transcripts in our northern hybridizations. Northern analyses with different probes revealed that these shorter forms included the MS2L and part of the 3' UTR 20 , indicative of premature transcription termination. Such cases are likely to reduce the efficiency of the isolation of proteins associated with the 3' UTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation